Parton energy loss without transverse momentum broadening - Zapp, Korinna Christine; Ingelman, G.; Rathsman, J.; Stachel, Johanna; Wiedemann, U. A. (Indian journal of physics, 2011)
The Jewel 1.0 Monte Carlo simulates jet evolution in a medium with a microscopic description of splitting and scattering processes. In the framework of this model we investigate the transverse momentum broadening due to medium effects in different scenarios. Depending on assumptions about hadronisation, we observe either a small increase or even a slight decrease of the mean transverse momentum, but no sizeable broadening. This appears to be a natural consequence of a model formulation which conserves energy and momentum microscopically at each splitting and at each scattering.